1999
DOI: 10.1046/j.1365-2133.1999.02927.x
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus ointment improves psoriasis in a microplaque assay

Abstract: Tacrolimus (FK506) is an effective and well tolerated immunosuppressant used to prevent allograft rejection. We describe the evaluation of two tacrolimus ointment formulations for treatment of chronic plaque-type psoriasis. This was a microplaque assay with randomized, double-blind design. Sixteen patients (15 men, one woman, all white and 28-69 years old) with chronic plaque-type psoriasis participated. Six different ointments were applied to discrete microplaques, 17 mm in diameter, on a descaled psoriasis l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
81
0
8

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(90 citation statements)
references
References 13 publications
1
81
0
8
Order By: Relevance
“…DIPA is used for cosmetics and drug formulations. 13,14) DIPA is an ester made of an aliphatic dicarboxylic acid of carbon number 6 (C6). DIPS is another aliphatic ester but has a dicarboxylic acid of C10.…”
Section: Discussionmentioning
confidence: 99%
“…DIPA is used for cosmetics and drug formulations. 13,14) DIPA is an ester made of an aliphatic dicarboxylic acid of carbon number 6 (C6). DIPS is another aliphatic ester but has a dicarboxylic acid of C10.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports demonstrated that topical application of FK506 ointment was only effective under occlusion or to some specific regions of the body where the skin was thinner and more permeable, such as the face and intertriginous areas. [23][24][25][26][27] The poor efficacy of FK506 for topical therapy was attributed to its high hydrophobicity and high molecular weight (822.05 Da), which prevent it from penetrating into and through the skin. In our previous study, 28 we have formulated a hybrid nanoparticle system for FK506 percutaneous delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Bu çalışmanın hemen ardından Remitz ve ark. topikal uygulanan %0,3 takrolimus, %0,005 kalsipotriol, %0,1 betametazonun plasebo ile karşılaştırmalı etkisini değerlendirmek için önceden %2 salisilik asitle inceltilen psoriatik plaklara bu ilaçları 2 hafta boyunca her 2-3 günde bir oklüzyonla uygulamışlardır 10 . Tedavi sonunda plasebo ile karşılaştırıldığında takrolimus uygulanan alanda eritem ve infiltrasyonda azalma izlenirken, kalsipotriol ile takrolimus arasındaki belirgin fark saptanmamıştır.…”
Section: Discussionunclassified
“…Psoriasiste topikal takrolimusun etkinliğinin değerlendirildiği çalışmalarda özellikle fasiyal, invers ve genital psoriasiste başarılı sonuçlar bildirilmiştir [5][6][7][8][9] . Bunun yanında kronik plak tipi psoriasiste etkinliği plaseboya benzer, plasebodan üstün ve potent steroidlere eşdeğer şeklinde çelişkili sonuçlar bildirilmektedir [10][11][12] . Son yıllarda topikal takrolimus tırnak tutulumunda da etkili olarak bildirilmiştir 13 .…”
Section: Introductionunclassified